Chemical Mechanical Polishing (CMP) of SiC Wafer Using Photo-Catalyst Incorporated Pad. (11th August 2017) - Zhou, Yan; Pan, Guoshun; Zou, Chunli; Wang, Lei
Abstract : Silicon carbide (SiC) is considered as the next generation key semiconductor material owing to its excellent properties. However, due to its high mechanical hardness and strong chemical inertness, SiC is very difficult to be polished. A novel photo-catalyst incorporated pad is developed for chemical mechanical polishing (CMP) of Si-face SiC wafer, in order to obtain higher removal rate (MRR) and smooth surface. The preparation of the photo-catalyst TiO2 incorporated pad is introduced, and the characteristics of the new pad are studied. CMP performances of SiC wafer using the catalyst incorporated pad and the conventional pad respectively under UV light are investigated. MRR by the catalyst incorporated pad is much higher than that by the conventional pad. Meanwhile, the low roughness ultra-smooth surface with atomic step structure could be obtained. The relative removal mechanism of chemical active pad toward the polished SiC surface is also discussed.